(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The processes of colonization and decolonization are both related to the introduction of the English language and literature in India. The colonial experience contributed to the change in women’s position in Indian society, which is reflected in women’s literature. Therefore, it would be interesting to see the postcolonial response of women writers to the life and experience of the modern Indian women. This dissertation seeks to find out the post-colonial features in the fiction of five Indian women writers in English of the post 1980s.The writers are Chitra Banarjee Divakaruni, Jhumpa Lahiri, Gita Mehta, Arundhati Royand Jai Nimbkar. The contribution by women writers to Indian fiction in English has its own place and significance. The origins of Indian literature in English may be traced back to the introduction of the English language in India by the British. Basically, it was an intentional, political and colonial action of the British rulers. These colonizers introduced English and its literature in India to inculcate western taste and culture in their colonial subjects. Their intention was to impose the superiority of western culture on the Indian mind. Indian fiction in English is rich in tradition and variety.